SECONDARY PREVENTION IN PATIENTS AFTER MYOCARDIAL INFARCTION AT AMBULATORY SPECIALIZED CARDIOLOGY INSTITUTION (PHARMACOEPIDEMIOLOGY STUDY) - S. B. Fitilev; I. I. Shkrebneva; A. V. Vozzhaev; D. A. Dimitrova (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To assess 5 years trend in level of doctor’s adherence to actual guidelines on secondary prevention of cardiovascular diseases in patients with a history of myocardial infarction in ambulatory specialized healthcare institution in Moscow. Material and methods. There were 752 patients firstly visited healthcare institution in 2006 and 825 patients – in 2011. Their data was included in two-stage retrospective pharmacoepidemiology study. Results. Prescription rate significantly increased for three of four prophylactic groups recommended for patients with a history of myocardial infarction (antiplatelets – 91.76%, beta-blockers – 83.39%, statins – 69.45%). When assessing prescribed doses of drugs, an increase in a number of their higher doses prescriptions was revealed (at the second stage of the study acetylsalicylic acid 100 mg/day received 75.32% of patients, enalapril 20 mg/day – 30.45%, simvastatin and atorvastatin 20 mg/day – 64.52% and 47.89% of patients, respectively). Conclusion. Results showed growing level of doctor’s adherence to actual recommendations on therapy and secondary prevention of cardiovascular diseases. Nevertheless, the level of adherence remains unsatisfactory and requires additional work with doctors.